Catechol–metal coordination-mediated nanocomposite hydrogels for on-demand drug delivery and efficacious combination therapy. (15th July 2021) - Dai, Guoru; Sun, Lu; Xu, Jing; Zhao, Guizhen; Tan, Zheng; Wang, Chen; Sun, Xiaolian; Xu, Keming; Zhong, Wenying
Abstract: Hydrogels have drawn considerable attention in the field of drug delivery, yet their poor mechanical strength and uncontrollable drug release behavior have hindered further applications in clinical practice. Taking utility of metal–ligand coordination for structurally reinforcing the hydrogel network, we report design and synthesis of magnetic nanocomposite hydrogels (HA-DOPA·MNPs) that are crosslinked by DOPA–Fe(III) coordination existing between dopamine-conjugated hyaluronan (HA-DOPA) and iron oxide magnetic nanoparticles (MNPs). The MNPs in the nanocomposite hydrogel not only serve as structural crosslinkers, but also facilitate magnetic hyperthermia and on-demand release of doxorubicin (DOX) in HA-DOPA·MNPs/DOX hydrogels, for release rate of DOX accelerates when external alternating magnetic field (AMF) is ON, and it restores to a slow pace when AMF is OFF. Importantly, HA-DOPA·MNPs/DOX hydrogel shows a longer retention time than HA-DOPA/DOX gel or DOX solution in vivo . Further experiments confirm the efficacious anticancer potency of HA-DOPA·MNPs/DOX in vitro and in vivo, that is mediated by a combination therapy consisting of chemotherapy (DOX) and hyperthermia (MNPs). In contrast, single-modality treatment (DOX or hyperthermia only) fails to show an equivalent efficacy at the same dose. Statement of significance: This study reports the design of a class of magnetic nanocomposite hydrogel (HA-DOPA·MNPs) that was structurally reinforced by DOPA–Fe (III) coordination between HA-DOPA and iron oxide MNPs. On one hand, MNPs served as crosslinking centers for structurally reinforcing the nanocomposite hydrogel; on the other hand, MNPs facilitated temperature rise under an external MNPs, which prompted on-demand drug release as well as a combination therapy. Comparing to single modality treatment (chemotherapy or hyperthermia alone), the HA-DOPA·MNPs/DOX formulation with AMF demonstrated better efficacy against proliferation of tumor cells (A375) both in vitro and in vivo . We believe that design of HA-DOPA·MNPs/DOX hydrogel in this report provides a general approach to fabricate structurally-reinforced nanocomposite hydrogels for on-demand drug delivery and efficacious combination therapy. Graphical abstract: Image, graphical abstract